1994
DOI: 10.1136/jcp.47.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of vascular injury in acute multiple sclerosis.

Abstract: Aims-To examine the vascular changes occurring in three archival cases of acute multiple sclerosis, and to provide immunohistochemical evidence of early endothelial cell activation and vascular occlusion in this condition. Methods-Central nervous system tissues from three cases of acute active multiple sclerosis and six non-inflammatory controls were stained using the following methods: haematoxylin and eosin, Luxol fast blue, cresyl violet, Bielschowsky's silver, and reticulin. Tissues were also inmunostained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 19 publications
3
90
1
Order By: Relevance
“…Recently it was shown that hypoxia-like tissue injury is an important pathogenic mechanism in lesion formation in a subtype of multiple sclerosis and virus encephalitis patients (43). This process is associated in part with damage and thrombotic occlusion of microvessels (44). Data on p75TNFR expression in such lesions, however, are still missing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that hypoxia-like tissue injury is an important pathogenic mechanism in lesion formation in a subtype of multiple sclerosis and virus encephalitis patients (43). This process is associated in part with damage and thrombotic occlusion of microvessels (44). Data on p75TNFR expression in such lesions, however, are still missing.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the estimates of prevalence of cognitive deficits in MS that range from 40 to 65%, with higher frequency in the chronic progressive clinical subtype (Heaton et al, 1985;Rao et al, 1991a). An ischemic component has long been acknowledged in histological studies of MS (Wakefield et al, 1994). Indeed, several mechanisms may lead to hypoxia-like tissue injury in MS. Cytotoxic T cells may recognize their antigen on endothelial cells and Figure 1 Scatter plot of the correlation between the mean deep gray matter (GM) CBF expressed in mL/100 g per min versus the mean Rey Complex Figure Test (RCFT) Z-score in patients with RR-MS (J) and in patients with PP-MS (~).…”
Section: Discussionmentioning
confidence: 99%
“…During inflammation, vascular dysfunction and local production of toxic metabolites may lead to defective microcirculation and subsequent ischemia, contributing to clinical manifestations (Wakefield et al, 1994). The assessment of cerebral hemodynamics has been made possible through MRI by using dynamic susceptibility contrast (DSC)-enhanced T2*-weighted MRI (Ostergaard et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, early vascular endothelial cell activation was identified prior to cerebral parenchymal reaction and demyelination [55], which, in combination with discrete microglial activation and perivascular cellular infiltrates, is a frequent finding in postmortem tissue of MS patients [56]. Microglial activation coincided with abnormal endothelial tight junctions in active lesions and normal appearing white matter, leading to putatively open junctions in microscopically inflamed vessels [57].…”
Section: Pathophysiological Considerationsmentioning
confidence: 99%